High lead level in the Alps in XIXth century, learning from the analysis of 138 historical hair stands. (January 2022) - Thomas, O.; Le Bot, B.; Verrey, D.; Durand, S.; Harpet, C.; Froment, A.; Jégou, B.
Abstract: Analysis of hair is known to provide useful information about environmental and toxic exposures. Very little historical use has been made of this type of investigation. Here we study 138 human hair samples from 19th century in France. In order to examine the potential association between contamination and historical health impacts, we characterized contamination by 33 elements in a set of hair strands sampled during the last quarter of the 19th century in the Savoy region of France. After a selected washing step on 138 hair strands conserved at the Museum National d'Histoire Naturelle in Paris (France), we assessed the presence of inorganics by ICP/MS, and lead level was higher than values reported in literature. We then compared concentrations and distributions between women and men, sampling locations and crossing gender and geographical origin. Hair lead level was high throughout Savoy at the end of the 19th century: significantly higher for people living in towns or industrial valleys, and lower for those of countryside and mountains areas. Environmental and economic changes (industrialization and urbanization with water adduction and leaded paints), living habits (kitchenware, cosmetics, wine, and tobacco), and local features (mines exploitation, railroad development, and industrialized narrow valleys) could be envisaged for explaining the level of lead contamination. In the same period, the two main industrial valleys of Savoy (Maurienne and Tarentaise) had high rates of endemic goiter and cretinism and among the highest hair lead levels. Other lines of evidence will need to be explore to investigate a possible link between historical Pb exposure and goiter in the study area. Graphical abstract: Image 1 Highlights: The analysis of 33 elements was carried out on 138 historical hair strands sampled around 1880 in the French Alps. The hair lead level (HLL) was higher than values reported in literature. HLL was depending on samples localization, and higher in town and industrial valleys than in mountains area and countryside.